ANÁLISIS E INTERPRETACIÓN DE LOS ESTADOS FINANCIEROS A LA FEDERACIÓN REGIONAL DE ASOCIACIONES DE PEQUEÑOS CAFETALEROS ECOLÓGICOS DEL SUR, DEL CANTÓN CATAMAYO, PERÍODO 2016 – 2017 - Cordova Shumi, Soraya Raquel (2019)
This thesis work called “ANALYSIS AND INTERPRETATION OF THE FINANCIAL STATEMENTS TO THE REGIONAL FEDERATION OF ASSOCIATIONS OF SMALL CAFETALEROS ECOLÓGICOS DEL SUR, DEL CANTÓN CATAMAYO, PERIOD 2016 - 2017”, was carried out in order to know the economic and financial performance of The Federation, with the fundamental purpose of analyzing and interpreting its financial statements, becoming an effective tool for the President and his partners to improve administrative and financial management, by making appropriate decisions. To comply with the specific objectives set for the development of the thesis work, the composition and structure were evaluated through vertical and horizontal analysis with the purpose of knowing the participation and variation of the different items that intervened in the States of Financial Status and Income Statement in the periods 2016 and 2017. Then, the main financial indicators were applied according to the need and operational activity carried out by the Federation, which were used to measure or quantify its economic and financial reality, determining those of liquidity that show the capacity it has is to generate cash and cover your short-term obligations; those of activity that allowed to determine the rotation of the merchandise, those of indebtedness, to know how stable and 5 consolidated the Federation is and those of profitability to measure the performance of the association in relation to its sales, assets or capital. In order to fulfill the third objective, the Financial Analysis Report was prepared where the conditions and financial position of FAPECAFES are disclosed. Given that it is profitable because it has utility in both periods analyzed and because the Federation is identified as industrial-commercial, the ideal would be that its structure is concentrated in the Current Assets, specifically in the Financial Assets and Inventories. Liquidity indicators were applied, resulting in the fact that once inventories of current assets are discounted, it does not exceed the established standards, obtaining a liquidity degree of $ 0.83 for 2016 and $ 0.37 for 2017, understanding that FAPECAFES needs expressly from the sale of inventories to meet its short-term obligations, in the indebtedness indicators it was known that the Federation is committed to 50.63% in 2016 and increases by 54.38% in the year 2017, which is high compared to the standard of such indicator that is less than 50%. Finally, the respective conclusions and recommendations, more relevant of the financial analysis, were established to achieve a better development of the Federation.